2013
DOI: 10.1103/physreva.87.032113
|View full text |Cite
|
Sign up to set email alerts
|

Local symmetries in one-dimensional quantum scattering

Abstract: We introduce the concept of parity symmetry in restricted spatial domains—local parity—and explore its impact on the stationary transport properties of generic, one-dimensional aperiodic potentials of compact support. It is shown that, in each domain of local parity symmetry of the potential, there exists an invariant quantity in the form of a nonlocal current, in addition to the globally invariant probability current. For symmetrically incoming states, both invariant currents vanish if weak commutation of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(79 citation statements)
references
References 31 publications
2
77
0
Order By: Relevance
“…quantum systems with local symmetries. It is only recently that it has been shown [11][12][13][14][15][16][17][18][19][20] that the unique feature of the presence of local symmetries are the existence of invariant two-point correlator currents. However, all of these works address the case of one-dimensional stationary and non-interacting wave mechanical setups ranging from acoustics, optics to quantum mechanics and make no statement how a more general concept of local symmetries could look like, in particular in the case of dynamically interacting quantum systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…quantum systems with local symmetries. It is only recently that it has been shown [11][12][13][14][15][16][17][18][19][20] that the unique feature of the presence of local symmetries are the existence of invariant two-point correlator currents. However, all of these works address the case of one-dimensional stationary and non-interacting wave mechanical setups ranging from acoustics, optics to quantum mechanics and make no statement how a more general concept of local symmetries could look like, in particular in the case of dynamically interacting quantum systems.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing to a single particle in one dimension which is the case previously treated extensively [11][12][13][14][15][16][17][18][19][20] we obtain…”
Section: Non-interacting Particle Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is a class of CLSs which are protected by spatial local symmetry of the Hamiltonian against any perturbations preserving this local symmetry and the geometry within their localization domain 10 . As a side note, the more general study of local symmetries has recently been put on new grounds by introducing a framework of nonlocal currents [29][30][31][32][33][34] by means of which the parity and Blochtheorem are generalized to locally symmetric systems 35 . Recently, it has been shown that CLSs may result from particular local symmetries which commute with the Hamiltonian in discrete systems 10 .…”
mentioning
confidence: 99%
“…In this way, the vanishing commutator condition satis…ed by the renormalized blocks is directly connected to the local mirror symmetry of the underlying atomic clusters, in agreement with the presence of a number of perfect transmission resonant states in general aperiodic systems exhibiting translation or inversion local symmetries. [57][58][59] Furthermore, from the graphical summary displayed in Fig.11 we realize that those BACs sharing the resonance energy E in their spectra (i.e, Fibonacci, precious mean and period doubling) have in common the presence of both T AAB and T BAA local transfer matrices in their renormalization block matrices, whereas those BACs lacking the resonance energy E in their spectra (i.e, metallic and mixed based means) include the conjugated local transfer matrices T BBA and T ABB as well due to the presence of B B bonds in addition to A A and A B ones. This is illustrated in the last column of Fig.11, where we compare the spectra obtained for the period doubling and copper limit-periodic crystals.…”
Section: Discussionmentioning
confidence: 99%